The Effect of Role Playing Learning Model on Students Historical Empathy at SMA Negeri 1 Bayah: Pengaruh Model Pembelajaran Role Playing terhadap Empati Sejarah Siswa di SMA Negeri 1 Bayah - Tubagus Umar Syarif Hadi Wibowo; Ana Nurhasanah; Dian Ami Astuti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to determine the effect of role playing learning model on historical empathy of class XI SMA Negeri 1 Bayah students. The method used was quasi experiment with non equivalent control group design. The research sample consisted of XI-4 (experimental) and XI-6 (control) classes. Data were collected through pre test and post test using historical empathy questionnaire. The results of the independent sample t-test showed a significant difference between the experimental and control groups (p = 0.042), which means that the role playing model is effective in increasing students' historical empathy.